Increasing Capital Income Share and its Effect on Personal Income Inequality - Branko Milanovic (Luxembourg Income Study (LIS), 2016)
Piketty's r>g implies an increase in capital-output ratio and in the share of capital income in net output. But it still does not guarantee the increase in personal income inequality. We derive the conditions for the "pass-through" of the rise in the share of capital income to greater personal income inequality. They have to do with the concentration of income from capital and its association with higher overall income. A key way to breaking the "transmission" into higher personal inequality is to diversify ownership of capital ("people's capitalism").
Keywords: 330